The Role of Malassezia Spp. in Pityrasis Versicolor: A Literature Review - Zahlah Levia Redini Umar; Dian Amelia Abdi; A. Sastri Zainuddin; Nurelly Noro Waspodo; Adharia Adharia (PSPP JOURNALS, 2026)
Pityriasis versicolor (PV) is a skin disease caused by the fungus Malassezia, common in tropical regions with high humidity, such as Indonesia. Pityriasis versicolor is characterized by hypopigmented or hyperpigmented patches, primarily on the chest, back, neck, and face, with some cases accompanied by itching. Risk factors include oily skin, immune conditions, genetics, and hot and humid environments. Further research is needed to understand the role of Malassezia in Pityriasis versicolor to improve treatment and prevent recurrence. To determine the role of Malassezia spp. in Pityriasis versicolor (PV) based on a literature review. Literature review with a narrative review design. Based on several reviewed journals, it can be concluded that Malassezia spp., which are part of the normal skin microbiota, can become pathogenic in individuals with certain predisposing factors. The transformation from yeast to hyphae, as well as the production of virulence factors such as lipase, protease, phospholipase, azelaic acid, melanin-like pigments, and the ability to form biofilms, play a role in the development of Pityriasis versicolor lesions. Interaction with the host occurs through direct mechanisms (irritant metabolites, keratinase) and immunological mechanisms (activation of inflammatory and allergic pathways), leading to skin barrier disruption, pigmentation changes, fine scaling, and potential alopecia. Variation in species and virulence profiles contributes to differences in clinical manifestations and responses to antifungal therapy. Malassezia spp. plays a key role in the development of Pityriasis versicolor through multifactorial virulence mechanisms and interactions with host predisposing factors, which influence clinical manifestations and treatment outcomes.